2007
DOI: 10.1088/0268-1242/22/8/010
|View full text |Cite
|
Sign up to set email alerts
|

Charge trapping characteristics of atomic-layer-deposited HfO2 films with Al2O3 as a blocking oxide for high-density non-volatile memory device applications

Abstract: Charge trapping characteristics of high-relative permittivity (high-κ) HfO 2 films with Al 2 O 3 as a blocking oxide in p-Si/SiO 2 /HfO 2 /Al 2 O 3 /metal memory structures have been investigated. All high-κ films have been grown by atomic layer deposition. A transmission electron microscope image shows that the HfO 2 film is polycrystalline, while the Al 2 O 3 film is partially crystalline after a high temperature annealing treatment at 1000 • C for 10 s in N 2 ambient. A well-behaved counter-clockwise capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(56 citation statements)
references
References 17 publications
2
50
0
Order By: Relevance
“…Nowadays, these oxide materials are commonly used as gate dielectrics in silicon-based microelectronics devices [1,3,4]. Due to a wide range of desirable properties, various dielectric oxides can also be applied as gate insulators in transparent devices with low power consumption, resistance switching materials for semiconductor memories, optical coatings in lasers and in microscopes or charge-coupled devices, and barriers and/or active layers in photovoltaic structures [5][6][7][8][9][10]. Dielectric thin films can be deposited using either RF-magnetron sputtering technology, chemical vapour deposition or atomic layer deposition (ALD) method [11][12][13][14], the method originally developed for the fabrication of amorphous Al 2 O 3 insulator films for electroluminescent flat panel displays [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, these oxide materials are commonly used as gate dielectrics in silicon-based microelectronics devices [1,3,4]. Due to a wide range of desirable properties, various dielectric oxides can also be applied as gate insulators in transparent devices with low power consumption, resistance switching materials for semiconductor memories, optical coatings in lasers and in microscopes or charge-coupled devices, and barriers and/or active layers in photovoltaic structures [5][6][7][8][9][10]. Dielectric thin films can be deposited using either RF-magnetron sputtering technology, chemical vapour deposition or atomic layer deposition (ALD) method [11][12][13][14], the method originally developed for the fabrication of amorphous Al 2 O 3 insulator films for electroluminescent flat panel displays [15].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, at this high temperature, the effect of charge-trap elimination by the PDA should dominate its effect on charge-trap generation. It has been reported that Al 2 O 3 film grown by ALD using Al(CH 3 ) 3 and H 2 O as as precursors was oxygen-rich [19]. Also, it was observed that Al 2 O 3 film grown by low-pressure chemical-vapor deposition using Al(CH 3 ) 3 and O 2 as precursors was non-stoichiometric with excess oxygen and its non-stoichiometry decreased after PDA, even at a low temperature of 500°C, due to out-diffusion of the excess oxygen [20].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Al 2 O 3 film grown by ALD using Al(CH 3 ) 3 and H 2 O as as precursors was oxygen-rich [19]. Also, it was observed that Al 2 O 3 film grown by low-pressure chemical-vapor deposition using Al(CH 3 ) 3 and O 2 as precursors was non-stoichiometric with excess oxygen and its non-stoichiometry decreased after PDA, even at a low temperature of 500°C, due to out-diffusion of the excess oxygen [20]. Therefore, in this work, during the PDA at 700°C, the excess oxygen in the Al 2 O 3 film should significantly diffuse into the GeON film to remove its defects (charge traps) by forming Ge-O bonds, and even convert remnant Ge-N bonds to Ge-O-N bonds, thus resulting in smaller program window and lower program speed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 To improve the Program/Erase (P/E) performance (erase speed and memory window closure) and data retention, Al 2 O 3 has been proposed as blocking layer, [13][14][15][16] giving rise to TaN/Al 2 O 3 /Si 3 N 4 /SiO 2 /Si (TANOS) charge-trap memories. [10][11][12][13][17][18][19][20][21][22][23][24] It has been reported that the density of as-grown electron traps in Al 2 O 3 , as other high-j dielectrics, is orders of magnitude higher than conventional SiO 2 . These traps contribute to the leakage current through the dielectric under low electric fields, due to trap-assisted-tunneling (TAT), which affects the reliability and data retention of the devices.…”
Section: Introductionmentioning
confidence: 99%